Law's empire - Dworkin, Ronald (New York Bloomsbury publishing, 2021)
In this reprint of Law's Empire, Ronald Dworkin reflects on the nature of the law, its given authority, its application in democracy, the prominent role of interpretation in judgment, and the relations of lawmakers and lawgivers to the community on whose behalf they pronounce For that community, Law's Empire provides a judicious and coherent introduction to the place of law in our lives.
Keywords: Law--Philosophy; Law; Jurisprudence; Common law; United States